The dismissal in the legislation and in the jurisprudence of the Constitutional Court and the Supreme Court Rulings on labor cases - Neves Mujica, Javier (2015)
The treatment of labor dismissal has been evolving in the legislation and in the jurisprudence. Whatis the current regulation of this subject? What is the procedure to ask for reparation in the case ofnon justified dismissal? These and other subjects related to this matter have been treated by the Constitutional Court and the Supreme  Court  inthe last binding precedents and in laboral courtrulings, respectively.Within this framework, the author illustrates us regarding the evolution of dismissal’s treatment in the legislation and recent jurisprudential pronouncements.